New Amphipoda crustaceans species recently found in Vietnam nearshore waters - Thanh, Dang Ngoc; Anh, Le Hung (Academia Journal of Biology, 2012)
Taxonomical study recently realized with materials collected from nearshore waters of Vietnam has contributed 7 new species to science, belonging to families: Amphithoidae, Corophiidae, Liljeborgidae, Lysianassidae and Synopiidae. Cymadusa exavata sp. n. (Figs. 1-16) Male: Body large in size. Anterofrontal margin with low ocular lobe. Eyes subquadrate, reddish. Antennae 1 and 2 subequal in length, reaching midpoint of body length. Antennae 1 with 1st and 2nd peduncular article similar in length. Flagellum 26-articulated, accessory flagellum 1 articulate. Antennae 2 with 4th as long as in length with 5th peduncular article, flagellum 24-articulated. Mandibule palp 3-jointed, 2nd and 3rd joints equal in length, with distal long seta. Gnathopod 1 (male) with 5th article cup form, 6th article large, subquadrate, palm transverse widely excavated, delimited by a strong tooth. Gnathopod 2 with slender, curve 2nd article. 5th and 6th article subequal in length, the later one subretangular, palm oblique, short. Claw like 7th article overeaching beyond palm. Uropod 1 with ramus unequal, lateral margin setose. Uropod 2 with equal ramus. Uropod 3 with rami longer than 1/2 peduncle. Telson quadrate distally setose. Female: Unknown. Kanaka quadrata sp. n. (Figs. 17-32) Male: Anterolateral cephalic lobe developed, reaching nearly distal margin of 3th peduncular article of Ant 2. Eyes large, occupied the whole cephalic lobe. Antennae 1, 2nd and 3rd peduncular articles subequal in length. Flagellum 8-articulated. Antennae 2 with 4th peduncular article very long, inflated, distal angle with a hooked tooth. 5th article stick shaped, 1/2 as long as 4th article. Gnathopod 1 with coxa anteriorly and posteriorly prolonging, 4th, 5th and 6th articles subequal in length. Gnathopod 2 with 2nd article slender, 5th subtriangular, 6th article widely quadrate, palm transverse, delimited by a strong tooth. Uropod 3 uniramus. Telson lobe medially excavated. Urosomit coalescent. Female: Sexual dimorphism in antennae 2, gnathopod 1 and 2 structures. Listriella tuberculata sp. n. (Figs. 33-50) Male: body small in size, whitish. Eyes round, large. Antennae 1 with 1st peduncular article large, 3rd article very small, flagellum 12-articulated, accessory flagellum 3-articulated. Antennae 2 with 4th and 5th peduncular articles equal in length. 14-articulated. Mandibule palp 3-jointed the 2nd the longest. Gnathopod 1 (male) with 5th article flat, cup form in shape, 6th ovate, palm overeaching midpoint of posterior margrin, setose and spinose, delimited 2 small tubercular spines. In proximal part near to basis occuring 3 large tubercules. Gnathopod 2 with similar structure, but 6th article with palm without tubercules at proximal part, only setose. Urosomit with a spine in dorsal margin. Uropod 1 with ramis subequal, longer than peduncle, outer ramus slender, biarticulate inter ramus lanceolate. Telson bilobed slender, distally spinose epimera 1-3 with poster distal angles untoothed. Pleonit segment dorsal margin smooth. Hippomedon pluriarticulatus sp. n. (Figs. 51-60) Male: body large in size. Dorsal margin without carina. Eyes large, reniform. Antennae 1 with 1st peduncular article longer than 2nd and 3rd article combined. Flagellum 16-jointed 1st joint very large. Accessory flagellum 6-articulated. Antennae 2 reaching to midpoint of body length, 4th peduncular article large subquadrate, shorter than 5th article, flagellum 46 articulate. Mandibule palp with 2nd joint the longest. Gnathopod 1 short, 5th and 6th articles subequal in length, 6th article subrectangular, palm tranverse distally located. Dactylus claw like, overeaching beyond palm, posterior margin armed with a spine. Gnathopod 2 long, 2nd article slender very long, 5th article 2 times as long as 6th, palm transverse distally located. Surface of 5th and 6th article densely setose. Claw like dactylus short, beak form. Uropod 1 and 2 rows of spines. Uropod 3 with rami longer than peduncle outer ramus biarticulate. Telson bilobed slender angle toothed. Epinera 3 with osterodistal. Hippomedon bioculatus sp. n. (Figs. 61-71) Male: body large in size, dorsal margin without carina. Head small, no rostrum. Eyes present with two distinct omnatidia. Antennae 1 with robust 1st article, 2nd and 3rd articles minute. Flagellum 7-articulated Antennae 2 short, reaching to 1/3 body length 4th and 5th articles equal in length, flagellum 26-jointed. Mandibule palp 3-jointed, 2nd and 3rd joints similar in length. Gnathopod 1 (male) with 5th article longer than 6th, this article elongate ovate in shape, palm oblique, reaching to 1/2 posterior margin delimited by a spine, palm margin scarcely setose. Claw like dastylus covered palm length. Gnathopod 2 with 5th longer than 6th article, this later subrectangular, densely setose on surface. Palm transvese, distally located in 6th article. Dactylus very short, beak form. Uropod 1 and Uropod 2 with rami equal peduncle, outer ramus biarticulate. Telson bilobed paralelly elongated. Epimera 3 with posterodistal angle produced to a minute tooth. Epimera 1, 2 with a spine in dorsal margin. Tiron quadrioculatus sp. n. (Figs. 72-86) Male: Dorsoanterior margin of head curving evenly to rostrum, without forming extended spine. lateral cephalic lobe round. Rostrum jointing obliquely anteroventrally. Eyes not presented, accessory eyes composed by 4 omnatidia. Antennae 1 with 2nd and 3rd articles equal in length. Flagellum 10-articulated, accessory flagellum 4-articulated. Antennae 2 with 4th peduncular article 2 times as long as 5th, flagellum 9-articulated. Mandibule palp with elongate 2nd joint. Gnathopod 1 and 2 (male) similar in structure, with 5th article slender, 2 times as long as 6th article. 6th article cylindrical, lateral inferior margin, as in 5th article, with rows of long setae. Claw like dactylus elongate. Pereopods 3-7 with short, cylindrical, 4-6 articles laterally armed with rows of spines and rudimentary distal dactylus. Uropods 1 and 2 with rami shorter than peduncle. Uropod 3 with rami longer than peduncle, outer ramus biarticulate, inner ramus with dense setose lateral margin. Telson with 2 slender lobes, slightly distally separated. Pleomit dorsal margin serrated. Urosomit 1, 2 with strong teeth in posterodorsal margin. Pseudotiron sublongicaudatus sp. n. (Figs. 87-100) Male: Body small in size. Dorsoanterior margin of head forming an extended forehead protuberance. Pleonit 1-5 with serrated posterodorsal margin. Antennae 1 peduncular article equal in length with 3rdarticle, 2nd article short, flgagellum 15-articulated, accessory flagellum 3-articulated. Antennae 2 with 5th peduncular article shorter than 4 article, flagellum 17-articulated, lateral margin peduncular articles setose. Mandibule palp with 2nd joint 2 times as long as 1st joint. Gnathopod 1 with 5th and 6th articles elongate, slender 6th article not diffenciated, 5th article 2,5 times as long as 6th article. Claw like dactylus elongate and toothed in ventral margin. Uropod 1 and 2 with rami longer than perduncule, inner ramus longer than outer, both biarticulate. Uropod 3 with unequal 2 ramus, lateral margin densely setose. Telson bilobed, slender, slightly separated distally. Urosomit 1-3 with poster dorsal marginal spines.